2006
DOI: 10.1002/gcc.20314
|View full text |Cite
|
Sign up to set email alerts
|

Allelotyping analysis at chromosome arm 8p of high‐grade prostatic intraepithelial neoplasia and incidental, latent, and clinical prostate cancers

Abstract: In this study, we used 7 informative microsatellite markers at 8p22, 23.1, and 23.2 in Japanese patients to compare frequency of loss of heterozygosity (LOH) in 53 lesions of high-grade prostatic intraepithelial neoplasia (HGPIN), 38 cases (38 lesions) of incidental prostate cancer (IPC), 31 cases (41 lesions) of latent prostate cancer (LPC), and 102 cases (168 lesions) of clinical prostate cancer (CPC). The frequency of LOH at 8p22-23.2 with at least 1 marker was 0%, 33%, 57%, and 51% in the HGPIN, IPC, LPC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
2
17
1
Order By: Relevance
“…Previously, we had performed a genome-wide search for LOH with human genetic markers in several types of cancer and confirmed that chromosomal alterations, especially deletions of some restricted regions, such as 8p22-23.1 and 13q14, are not only related with the initiation but also closely associated with subsequent progression of human cancers, especially in the metastasis of primary tumors. 21,22 The LOH at 6q16-22 and 10q22.3-23.1 tended to differ from the results of our previous allelotyping at 8p and 13q in the same samples.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Previously, we had performed a genome-wide search for LOH with human genetic markers in several types of cancer and confirmed that chromosomal alterations, especially deletions of some restricted regions, such as 8p22-23.1 and 13q14, are not only related with the initiation but also closely associated with subsequent progression of human cancers, especially in the metastasis of primary tumors. 21,22 The LOH at 6q16-22 and 10q22.3-23.1 tended to differ from the results of our previous allelotyping at 8p and 13q in the same samples.…”
Section: Discussioncontrasting
confidence: 84%
“…The LOH at 6q16-22 and 10q22.3-23.1 tended to differ from the results of our previous allelotyping at 8p and 13q in the same samples and another type of human cancer. [21][22][23][24] These results led us to suggest that LOH at 6q16-22 and 10q22.3-23.1 might not be a newly occurring genetic change during the progression from early stage prostate cancer to clinical significant prostate cancer even in the metastatic stage. Previously, we had performed a genome-wide search for LOH with human genetic markers in several types of cancer and confirmed that chromosomal alterations, especially deletions of some restricted regions, such as 8p22-23.1 and 13q14, are not only related with the initiation but also closely associated with subsequent progression of human cancers, especially in the metastasis of primary tumors.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition to HCC, the LOH on chromosome 8p has been implicated in other human cancers, including bladder cancer (27), breast cancer (28,29), B cell lymphoma (30), prostate cancer (31,32), and head and neck squamous cell carcinoma (33). Thus, the identification of candidate tumor suppressor genes on chromosome 8p and elucidation of their biological functions would be a significant advance in our understanding of tumorigenesis and progression.…”
Section: Introductionmentioning
confidence: 99%